Improved Hierarchical Structure Poly-particle particle Swarm Optimization - Hen C.K.; Paw J.K.S.; Ann Y.S.; Yan K.W. (2023)
In this paper, the Improved Hierarchical Structure Poly-particle Swarm Optimization (IHSPPSO) algorithm is proposed based on the Hierarchical Structure Poly-particle Swarm Optimization (HSPPSO) algorithm with the addition of three new operators, namely the Particle Repair Operator, Dynamic Acceleration Control Operator and Cauchy mutation operator to achieve better performance in terms of accuracy and rate of convergence. The performance of the IHSPPSO algorithm was tested and evaluated using four benchmark test functions. The test results of the IHSPPSO algorithm were compared with the ones of HSPPSO and significant improvements were shown. The addition of three new operators has significantly improved the performance of the IHSPPSO algorithm. 2012 IEEE.